Family Visit to Albert and Rose Watkins in Huntington Beach - Watkins, Howard::::::::: (1983)
Seated: Adam Watkins wearing Indian headdress, Rose Watkins, Jennifer Billey, Sammy Billey; Back: Albert Watkins, Pat Motts, Howard Watkins wearing Cherokee headdress, Christine Watkins, Lois Gardner, Lou Gardner in side yard End of roll of film